Skin capillary alterations in patients with acute SarsCoV2 infection. Issue 12 (18th December 2022) - Rosei, Claudia Agabiti; Gaggero, Andrea; Famà, Francesca; Malerba, Paolo; Chiarini, Giulia; Nardin, Matteo; Brami, Valeria; Rossini, Claudia; Coschignano, Maria Antonietta; Porteri, Enzo; Salvetti, Massimo; Muiesan, Maria Lorenza; et al.
Abstract : Background: Acute SarsCov2 infection is associated with endothelial dysfunction and 'endothelitis', which might explain systemic microvascular impairment. The presence of endothelial damage may promote vasoconstriction with organ ischemia, inflammation, tissue oedema and a procoagulant state resulting in an increase in the incidence of cardiovascular and cerebrovascular events. Microvascular thrombosis has been demonstrated in postmortem autopsy of COVID-19 patients; however, few data are available about skin capillary alterations in these patients. Materials and methods: We evaluated skin microvascular alteration in 22 patients admitted to our hospital with SarsCov2 infection. Capillary density was evaluated by capillaroscopy in the nailfold and the dorsum of the finger in the acute phase of the disease. Capillaroscopy was repeated after 3 months (recovery phase). In addition, blood chemistry parameters and inflammatory markers were obtained during acute infection and at the recovery after 3 months. Results: Patients with COVID-19 showed skin microvascular complications, such as thrombosis, microhaemorrhages and neoangiogenesis, which were not detected after 3 months from the discharge. A significant reduction of capillary density in the dorsum was observed after 3 months from the acute infection (97.2 ± 5.3 vs. 75.81 ± 3.9 n/mm 2 P < 0.05). A significant inverse correlation between C-reactive protein and capillary density was observed in patients with acute SarsCov2 infection ( r = 0.44, P < 0.05). Conversely a direct correlation between capillary density during the acute phase and lymphocyte number was detected ( r = 0.49, P < 0.05). Conclusion: This is the first in-vivo evidence of skin capillary thrombosis, microhaemorrhages and angiogenesis in patients with acute SarsCov2 infection, which disappeared after 3 months, supporting the presence of endothelial dysfunction and inflammation. Capillary alterations might reflect systemic vascular effects of viral infection.